Vim & Vigour : a show curated by MASS. - Brown, Sarah; Kemplen, Tony; S1 Artspace, Sheffield (Sheffield : MASS, 2004)
Aitken, Edwin ; Allen, Tim ; Alonso, Aiert ; Andrews, Chris ; Anon ; Atkinson, Terry ; Bainbridge, Terry ; Baines, Jenny ; Bartle, Richard ; Beierle, Norman ; et al.
Vim & Vigour, S1 Artspace, Sheffield
kunstcatalogus